(untitled) (Journal of actual problems of jurisprudence, 2018)
The Constitution in the community is a special place. The Basic Law, as the main political and legal document of the company, establishes the overriding political parties and socio-economic system, the organization of the state, defines the fundamental rights, freedoms and duties grazhdan.Segodnya constitutional rights has been translated into specific rules and laws have become part of everyday life . Thus, the Basic Law has laid the basis for further improvement of the legal mechanisms for the protection of human rights and created a legal foundation for the development of civil society in Kazakhstan. Keywords: Constitution, society, state, democracy.